Correlated Pc4–5 ULF waves, whistler‐mode chorus, and pulsating aurora observed by the Van Allen Probes and ground‐based systems. Issue 10 (28th October 2015) - Jaynes, A. N.; Lessard, M. R.; Takahashi, K.; Ali, A. F.; Malaspina, D. M.; Michell, R. G.; Spanswick, E. L.; Baker, D. N.; Blake, J. B.; Cully, C.; Donovan, E. F.; Kletzing, C. A.; et al.
Abstract: Theory and observations have linked equatorial VLF waves with pulsating aurora for decades, invoking the process of pitch angle scattering of tens of keV electrons in the equatorial magnetosphere. Recently published satellite studies have strengthened this argument, by showing strong correlation between pulsating auroral patches and both lower‐band chorus and tens of keV electron modulation in the vicinity of geosynchronous orbit. Additionally, a previous link has been made between Pc4–5 compressional pulsations and modulation of whistler‐mode chorus using Time History of Events and Macroscale Interactions during Substorms. In the current study, we present simultaneous in situ observations of structured chorus waves and an apparent field line resonance (in the Pc4–5 range) as a result of a substorm injection, observed by Van Allen Probes, along with ground‐based observations of pulsating aurora. We demonstrate the likely scenario being one of substorm‐driven Pc4–5 ULF pulsations modulating chorus waves, and thus providing the driver for pulsating particle precipitation into the Earth's atmosphere. Interestingly, the modulated chorus wave and ULF wave periods are well correlated, with chorus occurring at half the periodicity of the ULF waves. We also show, for the first time, a particular few‐Hz modulation of individual chorus elements that coincides with the same modulation in a nearby pulsating aurora patch. Such modulation has been noticed as a high‐frequency component in ground‐based camera data of pulsating aurora for decades and may be a result of nonlinear chorus wave interactions in the equatorial region. Key Points: Pulsating aurora can be produced by substorm‐driven ULF waves ULF waves drive VLF chorus waves, resulting in PA from pitch angle scattering Few‐Hz frequencies embedded in PA are also found in chorus elements